2014
DOI: 10.1016/j.egypro.2014.10.250
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Modeling of Solar Ponds

Abstract: A SGSP is a basin of water where solar energy is trapped due to an artificially imposed salinity gradient. In a SGSP three zones can be identified: the surface and bottom zones that are both convective and an intermediate zone in between which is intended to be non-convective. This zone acts as a transparent insulation and allows the storage of solar energy at the bottom where it is available for use.A numerical model where the SGSP dynamics is described in terms of velocity , pressure , temperature and salt c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…This study demonstrated that the pond's efficiency depends on the salt gradient's stability in the middle non-convecting zone. Giestas et al (2014) presented a numerical model using Computational Fluid Dynamics (CFD) to represent the dynamics of a SGSP. This model is based on the Navier-Stokes equations for incompressible fluids and linked with two advection-diffusion equations.…”
Section: Modeling Of Solar Pondsmentioning
confidence: 99%
“…This study demonstrated that the pond's efficiency depends on the salt gradient's stability in the middle non-convecting zone. Giestas et al (2014) presented a numerical model using Computational Fluid Dynamics (CFD) to represent the dynamics of a SGSP. This model is based on the Navier-Stokes equations for incompressible fluids and linked with two advection-diffusion equations.…”
Section: Modeling Of Solar Pondsmentioning
confidence: 99%
“…Bernad et al [30] developed a simulation tool for predicting solar pond performance and validated the results with experimental data obtained from operating a pilot plant in Martorell during 2009-2011. Giestas et al [31] presented a numerical model for predicting dynamics of the solar pond in terms of velocity, pressure, temperature, and salt concentration using Navier-Stokes equation for an incompressible fluid and one-advection diffusion equations for temperature and salt concentration. Monjezi and Campbell [32] developed a comprehensive model of the solar pond to predict temperature distribution of solar pond under Mediterranean conditions.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…One of the alternatives is to build a solar pond to absorb and store solar energy so that it can be used indefinitely. 5 The heat recovery from the ground below solar ponds was investigated by Ganguly et al 6 According to their result, the amount of heat recovered from the ground could be of significant quantity and this result is the same to that of the heat extracted from the lower convective zone (LCZ). According to a numerical study, 7 thermal storage time reduces by 47.5%, when conjugation of heat transfer between phase change material (PCM) and heat transfer fluid within the novel and efficient frustum-shaped thermal storage unit was compared with the traditional shell-and-tube unit with a single PCM.…”
Section: Introductionmentioning
confidence: 99%